Kecerdasan Emosional dan Kecanduan Internet pada Remaja di SMPN 3 2x11 Kayutanam Padang Pariaman - Sidaria Sidaria; Fitra Yeni; Muthmainnah Muthmainnah; Mutiara Hariyanto (Universitas Batanghari Jambi, 2023)
Uncontrolled and excessive use of the internet can have a negative impact in the form of internet addiction. Internet addiction can be experienced by anyone, especially teenagers. Teenagers are at the stage of identity crisis, tend to have a very high curiosity, and always want to try new things. One of the factors that influence internet addiction in adolescents is emotional intelligence. This study aims to determine the relationship between emotional intelligence and internet addiction in adolescents at SMPN 3 2x11 Kayutanam, Padang Pariaman Regency. This research method uses a correlation design with a cross sectional approach. The population in this study were students of SMPN 3 2x11 Kayutanam with a total sample of 110 respondents using the proportional strafied random sampling technique. The measuring tools used are The Schutte Emotional intelligence Scale for emotional intelligence and the Internet Addiction test for internet addiction. The results showed the average score of emotional intelligence was 118 which was moderate emotional intelligence and the average score for internet addiction was 42 which was mild internet addiction. The results of bivariate analysis using the Pearson showed p value = 0.000 and r value = -0.756 which means there is a significant relationship between emotional intelligence and internet addiction with a strong relationship strength in a negative direction. Which means that the higher the emotional intelligence, the lower the internet addiction.